Integrated O 2 and H 2 Gas Therapy via Microneedle‐Assisted Photocatalytic Water Splitting for Accelerating Diabetic Full‐Thickness Skin Wound Healing - Zesheng Chen; Yanchao Yu; Xingyuan Xiao; Wenwen Cheng; Ye Yang; Zhengyao Zhang; Wang Wang; Zhijun Zhou; Weikang Hu; Xiaolong Wang; Bing Li; Kwang Leong Choy; et al. (Advanced Science, 2026)
ABSTRACT Impaired wound healing in diabetes is closely associated with cellular ferroptosis. Microneedle‐assisted gas therapy exerts molecular regulation of ferroptosis, representing a promising approach for accelerating diabetic wound healing. To date, O 2 and H 2 gas therapies have consistently been conducted independently and have never been integrated into a single system. Whether and how their synergy might be realized remains a defining challenge. Herein, we propose a concept of integrated O 2 and H 2 gas therapy, demonstrated by fabricating a gas‐producing microneedle material. Platinum@MIL‐101(Fe)‐NH 2 @phosphotungstic acid (PMP) nanoparticles are synthesized as a visible light‐driven photocatalyst for H 2 and O 2 co‐evolution. The rational design of a spatially separated structure boosts their photocatalytic efficiency under physiological conditions. PMP nanoparticles are further incorporated with bilayer gelatin methacryloyl (GelMA)/PMP composite microneedles (denoted as GPM microneedles). The obtained GPM microneedles enable transdermal delivery of PMP nanoparticles for integrated O 2 and H 2 gas therapy, and demonstrate desirable biocompatibility and pro‐regenerative effects. The mechanism of integrated O 2 and H 2 gas therapy has been identified as a TNFAIP3/hnRNPA1 ubiquitination/ferroptosis signaling axis, establishing for the first time a direct link to ferroptosis. In conclusion, this study yields a transformative concept and a ferroptosis‐targeting microneedle material with well‐defined molecular mechanism for diabetic wound management.